Ageing prolongs inflammatory marker expression in regenerating rat skeletal muscles after injury - van der Poel Chris; Gosselin Luc E; Schertzer Jonathan D; Ryall James G; Swiderski Kristy; Wondemaghen Meron; Lynch Gordon S (BMC, 2011)
Abstract Background Some of the most serious consequences of normal ageing relate to its effects on skeletal muscle, particularly significant wasting and associated weakness, termed "sarcopenia". The underlying mechanisms of sarcopenia have yet to be elucidated completely but an altered muscle inflammatory response after injury is a likely contributing factor. In this study we investigated age-related changes in the expression of numerous inflammatory markers linked to successful muscle regeneration. Methods Right extensor digitorum longus (EDL) muscles from young (3 month), adult (12 month) and old (24 month) male F344 rats were injected with bupivacaine hydrochloride to cause complete muscle fibre degeneration, then excised 12, 24, 36, and 72 hours later (n = 5/age group/time point). We used qRT-PCR to quantify the mRNA expression levels of the inflammatory markers TNFα, IFNγ, IL1, IL18, IL6, and CD18 as well as regenerative markers MyoD and myogenin. Results Inflammatory markers were all increased significantly in all age groups after myotoxic injury. There was a trend for expression of inflammatory markers to be higher in uninjured muscles of old rats, especially at 72 hours post injury where the expression levels of several markers was significantly higher in old compared with young and adult rats. There was also a decrease in the expression of regenerative markers in old rats at 72 hours post injury. Conclusion Our findings identify a prolonged inflammatory signature in injured muscles from old compared with young and adult rats together with a blunted expression of key markers of regeneration in muscles of old rats. Importantly, our findings identify potential targets for future therapeutic strategies for improving the regenerative capacity of skeletal muscle during ageing.